Legal Challenges In The Age Of Social Media: Protecting Citizens From Misuse Of Information - Aka Akbar, Rivaldi; Mulyana, Aji; Amalia, Mia (Manunggal Halim Jaya, 2023)
social media has become an integral part of everyday life, bringing about positive impacts but also posing significant legal challenges. This research delves into the legal aspects of the social media era, particularly concerning the protection of citizens from information misuse. The phenomena of spreading false information, defamation, and insults are increasingly alarming, challenging the existing legal framework. This study aims to identify and analyze the legal challenges emerging in the era of social media, focusing on the protection of citizens from information misuse. The research employs a descriptive method with a qualitative approach to identify relevant legal frameworks. The analysis techniques include document analysis, comparison, and information synthesis. The result of the study highlights weaknesses in the existing legal framework and suggests policy updates to address emerging challenges. It is hoped that this research contributes to enhancing legal protection for citizens facing the risks of information misuse in the era of social media.